Integrating Artificial Intelligence to Enhance Writing Proficiency: An Exploratory Study of EFL Students’ and Instructors’ Perspectives at a University Level in Lebanon - Ayoub, Nawal Nabih; Joudi, Nadine Sami; Saba, Miriama Salim Bou; Saba, Anthony Salim Bou (European Scientific Journal, ESJ, 2025)
This paper focuses on scrutinizing the attitudes and opinions of English as a Foreign Language (EFL) learners and instructors on the integration of artificial intelligence (AI) in a writing skills course at a university level in Lebanon. Specifically, it examines AI as a pedagogical tool that provides personalized learning, supplies consistency in evaluation, furnishes enhanced feedback quality by offering detailed, instant feedback on grammar, style, and structure, and helping students refine their writing more efficiently. Moreover, it furnishes instructors with adaptive activities and assessments, thus making writing more engaging and more effective. It also seeks to evaluate students’ and instructors’ perspectives on AI’s vigorous role in learning. In this exploratory study, a mixed-method design and a convenient sampling of participants were utilized. A total of 51 EFL students and 8 instructors at the American University of Science and Technology in Lebanon during the spring semester of 2023-2024 participated in the study. To describe and quantify their perceptions of integrating AI in a writing course, two online surveys, including closed-ended and open-ended questions, and four focus group discussions were administered. The overall qualitative and quantitative analyses of the data indicated that Lebanese EFL students and instructors have positive attitudes towards integrating AI in a writing course as a pedagogical tool and as a fundamental part of the teaching strategies in EFL higher education classes since it provides helpful resources and aids learners to write effectively and build their self-confidence. However, the findings also revealed the need to train instructors and students to use AI technologies, keeping in mind the indispensable role of the instructor in class and the need for students to unleash their creativity.